Implementing an Online Reporting System in the Anatomical Pathology Department of a Tertiary Care Teaching Hospital in India:A Case Study. - Radhakrishna, Kedar; Correa, Marjorie; Thounaojam, Deepak; S. Raj, Tony D. (Perspectives in Health Information Management)
This article presents a case study in designing, developing, and implementing a web-enabled reporting application for the anatomical pathology (histopathology) department of a tertiary care teaching hospital in India. The article describes workflows, requirements assessment, and implementation methods that the investigators adopted for deploying the solution. The primary focus of the study was to demonstrate the requirements assessment performed, the strategies adopted, and the challenges encountered during the development and implementation. The study demonstrates a successful deployment as well as successful adoption of healthcare information technology by the end users. Factors that played a crucial role in adoption included the combination of people, processes, and technology. The lessons learned from this study would help application developers design efficient systems that suit the requirements of the end users while keeping in mind the ever-changing need for workflows and scalability in a developing country.